Microcredit Repayment among Smallholder Farmers: What Microfinance Institutions Need to Know - Jumpah, Emmanuel Tetteh; Tetteh, Emmanuel Kojo; Adams, Abdulai (Asian Journal of Agriculture and Rural Development, 2018)
Microcredit default among borrowers has been rising in recent years but empirical evidence to ascertain the factors determining repayment remain lacking especially in developing countries like Ghana. This study contributes to addressing this knowledge gap. The study used data of 224 microcredit borrowers from Ada West and Ada East districts to analyse factors determining repayment rate among smallholder farmer borrowers. Applying the logistic regression model, farmer and credit specific characteristics were used to analyse the determinants of microcredit repayment. From the logistic regression, age, gender, income, and number of dependants increase the likelihood of repayment. However, membership of farmer based organization, experience, interest rate, and duration of loan repayment negatively influences loan repayment. The study also found delays in loan disbursement resulted in loan use for unproductive ventures and repayment challenges. In addition, lack of training for borrowers on credit management, and investment procedures adversely impacted on loan repayment. The paper recommends that MFIs should institute measures to train borrowers on loan utilization, focus on women clients, since they have higher probability of repayment, reduce interest rate as well as putting in place mechanisms to reduce cost of operations.